Medical biotechnology: prospects in Malaysia - Isa, Nur Firdaus (Faculty of Biosciences and Medical Engineering, Universiti Teknologi Malaysia (UTM), 2018)
The blooming interdisciplinary research in Science, Technology, Engineering and Mathematics (STEM) is well-received by scientists who perceived this as a massive opportunity to the great era of medical biotechnology. In Malaysia, tropical diseases, vector borne diseases, and endemic infectious diseases are commonly associated with our population, but its pathogenesis and how we address it at the molecular level is still lacking.